Barriers affecting sustainable agricultural productivity of smallholder farmers in the Eastern Free State of South Africa - Myeni, L.; Moeletsi, M.; Thavhana, M.; Randela, M.; Mokoena, L. (MDPI, 2019)
Sustainable Agricultural Practices (SAPs) are the most promising pathways to enhance the productivity and resilience of agricultural production of smallholder farming systems while conserving the natural resources. This study was undertaken to identify the barriers affecting sustainable agricultural productivity of smallholder farmers in the eastern Free State, South Africa. Data were collected from 359 smallholder farmers using questionnaires and the validity of the collected data was confirmed through focus group discussions with key informants. Descriptive statistics and a binary logistic regression model were used to analyze data. Results indicated that traditional SAPs such as intercropping, mulching and crop rotation were more likely to be adopted by farmers with access to land yet without access to credit (and had low levels of education, although this finding was not significant). In contrast, new SAPs such as cover cropping, minimum-tillage, tied ridging and planting pits were more knowledge (education), capital and labor intensive. Therefore, extension strategies should take these differences into consideration when promoting both the adoption of traditional SAPs and new SAPs. Targeting resource-constrained farmers (in terms of access to credit and education) through raising awareness and building capacity is essential to ensure the adoption of traditional SAPs. In turn, promoting the adoption of new SAPs not only needs awareness raising and capacity building but also must fundamentally address resource constraints of South African smallholder farmers such as knowledge, capital and labor. It is recommended that government should provide resources and infrastructure to improve the quality and outreach of extension services through field demonstration trials and training.